2003
DOI: 10.1164/rccm.200212-1468oc
|View full text |Cite
|
Sign up to set email alerts
|

Airflow Obstruction after Myeloablative Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Despite advances in the management of myeloablative allogeneic hematopoietic stem cell transplants, airflow obstruction (AFO) remains a significant complication. We conducted a 12-year study to examine the recent epidemiology of AFO and its associated mortality. Using the rate of percent predicted FEV1 decline after transplant, we defined AFO as a more than 5% per year decline in percent predicted FEV1 with the lowest post-transplant FEV1/FVC ratio less than 0.8. New obstruction was more frequent than previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
262
3
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 234 publications
(279 citation statements)
references
References 51 publications
10
262
3
3
Order By: Relevance
“…In agreement with other previously published studies, 2,4,6,14,15 we found that nearly all patients who developed new-onset airflow obstruction after HSCT had chronic GVHD, suggesting that PTCB is a pulmonary manifestation of GVHD. Low levels of serum IgG and history of viral infections were also associated with this disease.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with other previously published studies, 2,4,6,14,15 we found that nearly all patients who developed new-onset airflow obstruction after HSCT had chronic GVHD, suggesting that PTCB is a pulmonary manifestation of GVHD. Low levels of serum IgG and history of viral infections were also associated with this disease.…”
Section: Discussionsupporting
confidence: 93%
“…2,3 Post transplantation constrictive bronchiolitis (PTCB) is the most common pulmonary complication among long-term survivors that may lead to progressive respiratory insufficiency and even death. [2][3][4][5][6] Due to the lack of uniform diagnostic criteria, the reported incidence of PTCB varies from 10 to 26%. 4 The most commonly identified risk factors are chronic GVHD, older age, viral respiratory infections during the first 100 days after transplantation, airflow limitation before transplantation and low level of serum IgG.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These facts limited the standardization of Palmas's criteria and individual reports of LONIPCs use different classification criteria. 8,9,12 Recently, several studies have revealed many risk factors that are associated with the onset of LONIPCs, including cGVHD, 9,[12][13][14][15][16][17][18][19] donor and recipient age, 13 baseline pulmonary function, 13 use of TBI, 20 and so on. There is a general agreement that cGVHD is the most strongly associated risk factor.…”
Section: Introductionmentioning
confidence: 99%
“…There is a general agreement that cGVHD is the most strongly associated risk factor. 9,[12][13][14][15][16][17][18][19] Although patients with LONIPCs have high nonrelapse mortality (NRM) rates, 9,12 they experience low relapse rates of the underlying disease presumably because high concomitant rates of cGVHD exert a graft-vs-tumor effect. 9 Thus, it remains unknown whether the onset of LONIPCs has an impact on OS or relapse-free survival as a consequence of these contradictory factors.…”
Section: Introductionmentioning
confidence: 99%